Avaliação de políticas de gestão da manutenção baseadas na mitigação de riscos considerando critérios de disponibilidade e produtividade - Alonso, Samanta de Lima (Universidade Federal de São Carlos, 2022)
Production systems were transformed by the advances of the Industrial Revolutions. In order to keep up with technological progress and achieve desired productivity levels, maintenance management has become a key factor for organizations. Since every production system is prone to failures in its equipment, directly impacting the reduction of manufacturing capacity, it is necessary to properly use maintenance policies to keep a system in good operating condition. In this sense, it is understood that the greater the availability of equipment, the greater the productivity of the system. Thus, the present work aims to incorporate risk mitigation applied together with the modeling and simulation of discrete events as tools to support decision-making for maintenance policies that lead to increased availability and manufacturing productivity. For this, an industrial system prone to machine failures and belongs to the public administration was analyzed. In the case studied, the proposed scenarios considered that the inclusion of preventive maintenance policies with a bimonthly or quarterly frequency projects both an increase in the Mean Time Between Failures of corrective maintenance and a reduction of the Mean Time to Repair of preventive maintenance due to the anticipation of administrative procedures previously planned. The workstations submitted to such proposals were Workstation A, Workstation B and Workstation E, defined according to the risk matrix resulting from the relationship between the Annual Frequency of Failures and the Impact of Machine Unavailability. In the case of productivity, there was a gain of 10.4% in parts of the simulated products and a gain of 6.2% in subsets. In the case of availability, there was a gain of 50% in availability in Workstation A, 62% in availability in Workstation B and 41% in availability in Workstation E. Therefore, this research fills a gap in the literature by applying the modeling and simulation of discrete events in a risk analysis approach associated with maintenance management. In this way, it was possible to develop a ranking of workstations priorities and types of failure to be included in preventive maintenance policy proposals, resulting in availability and productivity gains for the studied production system.
Evaluation of maintenance management policies based on risk mitigation considering availability and productivity criteria
Keywords: Manutenção; Análise de riscos; Produtividade; Disponibilidade; Simulação a eventos discretos; Maintenance; Risk; Assessment; Productivity; Availability; Discrete event simulation; ENGENHARIAS::ENGENHARIA DE PRODUCAO::PESQUISA OPERACIONAL